1999
DOI: 10.1093/ptj/79.1.66
|View full text |Cite
|
Sign up to set email alerts
|

Quadriceps Femoris and Hamstring Muscle Function in a Person With an Unstable Knee

Abstract: Background and Purpose. The purpose of this case report is to describe the evaluation, treatment, and short-term outcome for an individual with chronic, progressively worsening instability of the knee during gait associated with anterior cruciate ligament (ACL) insufficiency. Case Description. The patient was a 34-year-old man who sustained bilateral ACL injuries. Subsequently, an autograft reconstruction of the left knee ACL was performed. Eight months post-reconstruction, the left knee was unstable despite b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 31 publications
0
4
0
4
Order By: Relevance
“…115,116 Studies report large magnitude increases in quadriceps strength secondary to EMG biofeedback isometric training in individuals with ACLR and knee OA. [117][118][119][120][121] Both immediate (single bout) 116,117 and training effects (6-8 wk of intervention) 118,120,121 are reported. Although there is a lack of definitive evidence supporting EMG biofeedback over exercise alone, 122 it is worth noting that other forms of muscle-directed biofeedback, such as musculoskeletal ultrasound, are reported to have similar effects in those with knee OA.…”
Section: Acute Recoverymentioning
confidence: 99%
“…115,116 Studies report large magnitude increases in quadriceps strength secondary to EMG biofeedback isometric training in individuals with ACLR and knee OA. [117][118][119][120][121] Both immediate (single bout) 116,117 and training effects (6-8 wk of intervention) 118,120,121 are reported. Although there is a lack of definitive evidence supporting EMG biofeedback over exercise alone, 122 it is worth noting that other forms of muscle-directed biofeedback, such as musculoskeletal ultrasound, are reported to have similar effects in those with knee OA.…”
Section: Acute Recoverymentioning
confidence: 99%
“…The use of EMGBF in conjunction with exercise has been reported to positively affect both quadriceps activation 18,21,65,66 and strength. [18][19][20]22,23,[66][67][68] In a study that assessed the effectiveness of EMGBF in postoperative patients who underwent meniscectomy, their quadriceps activation was increased 10fold compared to patients who performed standard rehabilitation. Likewise, Maitland et al 66 conducted a case study of a patient who was 8 months after ACL reconstruction and reported progressively declining knee stability.…”
Section: Emgbf In Rehabilitationmentioning
confidence: 99%
“…[18][19][20]22,23,[66][67][68] In a study that assessed the effectiveness of EMGBF in postoperative patients who underwent meniscectomy, their quadriceps activation was increased 10fold compared to patients who performed standard rehabilitation. Likewise, Maitland et al 66 conducted a case study of a patient who was 8 months after ACL reconstruction and reported progressively declining knee stability. They found that by incorporating EMGBF into a closed kinetic chain rehabilitation program, the patient's quadriceps activation was improved by 52% and their peak torque during knee extension was increased by 203%.…”
Section: Emgbf In Rehabilitationmentioning
confidence: 99%
“…A difference in activation patterns between quadriceps and hamstrings has been demonstrated. Adjustments in neuromuscular factors due to injury may contribute to the more obvious impairments, such as strength loss, atrophy, and altered function (Chmielewski, Stackhouse, Axe, & Snyder-Mackler, 2004;Drechsler, Cramp, & Scott, 2006;Maitland, Ajemian, & Suter, 1999;McHugh, Tyler, Nicholas, Browne, & Gleim, 2001;Swanik, Lepart, Giraldo, DeMont, & Fu, 1999; Snyder-Mackler, De Luca, Williams, Eastlack, & Bartolozzi, Individual cycle lengths were normalized for a 28-day cycle for these graphical purposes (Wojtys et al, 2002). 1994; Urbach, Nebelung, Becker, & Awiszus, 2001;Urbach, Nebelung, Weiler, & Awiszus, 1999).…”
Section: Acl Injury Mechanismsmentioning
confidence: 99%